UPAYA PENGEMBANGAN PROFESIONALISME GURU DALAM MENINGKATAKAN KUALITAS MADRASAH - Pasmah Chandra (STIESNU Bengkulu, 2020)
ABSTRACT The problems faced by Madrasas have been an interesting subject from the past until now. Madrasa seems to be education number 2 (two) or in other words it can be called an alternative education institution. One of the problems faced by madrasas is related to the quality of teachers as human resources in building these educational institutions. Some previous studies have not emphasized the problem of teacher professionalism as the main problem faced by madrasas. The purpose of this study is to determine the quality of madrasas and professionalism of teachers. This type of research is qualitative research. The results of the study indicate that madrasa educational institutions strive to catch up with schools under the auspices of the Ministry of Education and Culture which is far more advanced. The teacher plays an important role in the success of curriculum implementation, because it is the teacher who will ultimately implement the curriculum in the classroom. Teachers are at the forefront in implementing curriculum. Even though the curriculum and education system has been good, without the support of the quality of qualified teachers, everything will be in vain. Improving the quality of education in Indonesia, especially madrasas, is not enough to improve the curriculum, but must also be followed by improving the quality or professionalism of teachers at primary and secondary levels. Keywords: Madrasa Quality, Teacher Professionalism. ABSTRAK Permasalahan yang dihadapi oleh Madrasah telah menjadi pokok yang menarik sejak dahulu hingga saat ini. Madrasah seolah menjadi pendidikan nomor 2 (dua) atau dengan kata lain bisa disebut sebagai lembaga pendidikan alternatif. Salah satu permasalahan yang dihadapi oleh madrasah ialah berkaitan dengan kualitas dari guru sebagai sumber daya manusia dalam membangun lembaga pendidikan tersebut. Beberapa studi terdahulu belum menitikberatkan permasalahan profesionalisme guru sebagai masalah utama yang dihadapi madrasah. Adapun tujuan dari penelitian ini ialah untuk mengetahui kualitas madrasah dan profesionalisme guru. Jenis penelitian yang dilakukan ialah penelitian kualitatif. Hasil dari penelitian menunjukkan bahwa lembaga pendidikan madrasah berupaya untuk mengejar ketertinggalan dengan sekolah di bawah naungan Kementerian Pendidikan dan Kebudayaan yang jauh lebih maju. Guru memegang peranan penting terhadap keberhasilan implementasi kurikulum, Karena gurulah yang pada akhirnya akan melaksanakan kurikulum di dalam kelas. Gurulah garda terdepan dalam implementasi kurikulum. Walaupun kurikulum dan sitem pendidikan telah baik, namun tanpa didukung mutu guru yang memenuhi syarat maka semuanya akan sia-sia. Peningkatan kualitas pendidikan di Indonesia khususnya madrasah tidak cukup dengan pembenahan di bidang kurikulum saja, tetapi juga harus diikuti dengan peningkatan mutu atau profesionalisme guru di tingkat-tingkat dasar dan menengah. Kata Kunci: Kualitas Madrasah, Profesionalisme Guru.